Scotland - MacAndrew, Richard (United Kingdom Cambridge University Press, 2009)
From the Highlands to its islands, from terrifying tales of history to its modern cities such as Edinburgh and Glasgow, Scotland has a fascinating story to tell. Explore the country through its fantastic festivals, innovative inventions, and much more.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Reading books; Language Learning; Lower-intermediate Level; Fantasy; Fiction